2013
DOI: 10.1097/tp.0b013e318293b7b8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Transplant Outcomes in Diabetic Nude Mice Receiving Human, Porcine, and Nonhuman Primate Islets

Abstract: Background In the absence of a reliable islet potency assay, nude mice transplant is the criterion standard to assess islet quality for clinical transplantation. There are factors other than islet quality that affect the transplant outcome. Methods Here, we analyzed the transplant outcomes in 335 nude mice (NM) receiving islets from human (n=103), porcine (n=205), and non-human primate (NHP) donors (n=27). The islets (750, 1000, and 2000 islet equivalents) were transplanted under the kidney capsule of strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 27 publications
3
26
0
1
Order By: Relevance
“…29,30 However, our in vitro and in vivo functional assessments indicated that the YDP islet integrity and function were intact and not compromised. Increased protease dose necessitates the use of multiple vials of protease, which eventually increase the enzyme cost to isolate islets.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…29,30 However, our in vitro and in vivo functional assessments indicated that the YDP islet integrity and function were intact and not compromised. Increased protease dose necessitates the use of multiple vials of protease, which eventually increase the enzyme cost to isolate islets.…”
Section: Discussionmentioning
confidence: 75%
“…Islets isolated utilizing IPC from whole pancreas were carefully assessed by measuring viability and function quality, using FDA/PI and GSIR by both static and dynamic glucose challenges respectively. 29 Thirty days after transplantation, the graft-bearing kidney was removed to confirm graft function and stained for H&E (hematoxylin and eosin) and insulin. 28 In addition, 2000 IEQ human islets (after overnight culture) from the IPC group were transplanted under the kidney capsule of diabetic nude mice (n = 22) as described earlier.…”
Section: In Vitro and In Vivo Islet Assessmentmentioning
confidence: 99%
“…The need for more than one donor places islet transplantation in contrast to wholepancreas transplantation. Previous clinical (8,9) and basic science (10) studies have identified factors associated with increased islet potency and insulin independence after single-donor islet infusion. Aside from the stress placed on the donor organ pool, receiving islet transplantation from more than one donor increases the risk of recipient sensitization to human leukocyte antigens (7).…”
mentioning
confidence: 99%
“…Three days after the induction of diabetes, islets thawed after cryopreservation (2,000 or 4,000 islet equivalents [IEQ]) or freshly isolated islets (3,000 IEQ) were transplanted under the kidney capsules of the mice [32]. Their body weight and blood glucose levels were monitored over 10 weeks.…”
Section: Methodsmentioning
confidence: 99%